Non-invasive cardiac imaging for evaluation of cardiotoxicity in cancer patients - early detection and follow-up - Vorobiof, Gabriel; Silverstein, Cheri (SA Heart Journal, 2017)
Cardiotoxicity is an increasingly important clinical entity that occurs as a result of untoward, and incompletely understood, effects on cardiac function. It is primarily caused by the anthracycline agents (doxorubicin, daunorubicin) but has also been observed with monoclonal antibody agents such as trastuzumab and small molecule tyrosine kinase inhibitors. The most feared net result of these agents is left ventricular (LV) dysfunction resulting in symptomatic congestive heart failure (CHF). Other manifestations can include arrhythmias, pericardial constriction, valvulopathy and hypertension. Standard cardiac imaging techniques have largely focused on LV ejection fraction (LVEF) quantifi cation. Contemporary cardiac imaging technologies now exist that are capable of evaluating for and detecting earlier stages of cardiotoxicity, including those which occur prior to changes in LVEF. Therapeutic algorithms have been devised to tailor chemotherapeutic regimens based on these results and have resulted in a dramatically reduced incidence of overt CHF.